INTERNAL FACTORS OF COMPANY RATING ON FOOD AND BEVERAGE COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Heriansyah, Kurnia (STIE Kusuma Negara, 2019)
This research aimed to examine the influence of internal factors on firm value. In this study the internal factors that profitability, dividend policy, and funding decisions. This study used six companies as a sample from a population of 14 manufacturing companies listed on Indonesian stock exchange in period of 2011-2015. The sample was determined by using purposive sampling. The results showed that profitability and funding decisions had positive effect on firm value, while dividend policy had a negative effect on firm value. The profitability, dividend policy, and funding decisions simultaneously had a positive effect on firm value. The value of the adjusted R2 of  0,798 indicated that the contribution of all the independent variables to account for the dependent variables was 79,8%.